Boldine Supplementation Regulates Mitochondrial Function and Oxidative Stress in a Rat Model of Hepatotoxicity - Reza Heidari; Mohammad Reza Arabnezhad; Mohammad Mehdi Ommati; Negar Azarpira; Elham Ghodsimanesh; Hossein Niknahad (Tabriz University of Medical Sciences, 2019)
Background: The xenobiotics-induced liver injury is a clinical complication. Hence, finding new hepatoprotective strategies has clinical value. Oxidative stress and its subsequent complications are major mechanisms involved in xenobiotics-induced hepatotoxicity. Boldine is one of the most potent antioxidant molecules widely investigated for its protective properties in different experimental models. In the current study, the hepatoprotective properties of boldine and its potential mechanisms of hepatoprotection have been investigated. Methods: Rats received thioacetamide (TAA; 200 mg/kg, i.p) as a model of acute liver injury. Boldine (5, 10, 1nd 20 mg/kg; 24 hours intervals; oral) was administered as the hepatoprotective agent. Results: Liver injury was evident in TAA-treated animals (48 hours after TAA exposure) as a severe increase in serum level of liver injury biomarkers and histopathological alterations. Moreover, markers of oxidative stress were increased in liver tissue of TAA-treated rats. Assessment of mitochondrial indices of functionality revealed a significant decrease in mitochondrial dehydrogenases activity, the collapse of mitochondrial membrane potential, mitochondrial swelling and depletion of ATP content. It was found that boldine supplementation mitigated liver tissue markers of oxidative stress and improved mitochondrial indices of functionality in TAA-treated animals. Conclusion: The hepatoprotective properties of boldine might primarily rely on antioxidant and mitochondria protecting effects of this alkaloid.